2023
DOI: 10.1108/jtf-04-2023-0100
|View full text |Cite
|
Sign up to set email alerts
|

Meatless gastronomy: a threat or an opportunity for tourism development?

Josef Lochman,
Jiří Vágner

Abstract: PurposeMeat overconsumption by tourists is one of the key issues in the sustainability of tourist destinations. The objective of this paper is to assess the impact that a promotion of meatless gastronomy and its actual increased availability would have on the attractiveness and visitation of a popular European urban destination.Design/methodology/approachThe research uses an innovative foresight approach that combines environmental scanning and scenarios. The authors formulated the scenarios using the Delphi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…Meat overconsumption by tourists is one of the key issues affecting the sustainability of tourist destinations. Lochman and Vágner's (2024) paper sets out to assess the impact that a promotion of meatless gastronomy and its actual increased availability would have on the attractiveness and visitation of a popular European urban destination. Using a scenario-based approach, the authors found that a meatless image represents an opportunity for the future development of an urban European destination.…”
Section: Food Consumption and Communitiesmentioning
confidence: 99%
“…Meat overconsumption by tourists is one of the key issues affecting the sustainability of tourist destinations. Lochman and Vágner's (2024) paper sets out to assess the impact that a promotion of meatless gastronomy and its actual increased availability would have on the attractiveness and visitation of a popular European urban destination. Using a scenario-based approach, the authors found that a meatless image represents an opportunity for the future development of an urban European destination.…”
Section: Food Consumption and Communitiesmentioning
confidence: 99%